Staffing Data Processing at Universitas Sawerigading - Dety Junita Sulanjari; Djohar Djohar; Andi Pasong; Ahmad Syaekhu (Jurnal Ad'ministrare, 2021)
Personnel data management through the personnel management information system is all process activities carried out by an operator or an administrator in a WEB-based application that is designed as a solution to handle various matters in managing personnel data. Given the importance of managing employee data, improving the quality of personnel data management through a system is one of the priorities in the e-Government development stage. Good employee management will improve employee performance in an agency. This study aims to determine the processing of personnel data through information systems at Universitas Sawerigading. This research uses quantitative method with descriptive research type. The respondents in this study were 35 people. Data was collected using observation, questionnaires and documentation techniques. The data analyzed is the data obtained based on the respondents' answers. The results showed that the staffing data processing was in a fairly good category. From the aspect of data collection, data management, data storage and data reporting.